The Effects of National Business Systems on Human Resource and Payroll Administration – A Comparative Study of Germany and the - Dickmann, Michael; Tyson, Shaun (Cranfield University, 2003)
Organisations use an increasing number of national and international in-company shared service centres and outsourcing arrangements in the quest for efficiency improvements. A prime candidate for standardisation are administrative activities in which firms take advantage of the rapidly evolving information technology. This pull towards convergence is subject to a counter-force of national regulations, institutions and cultural factors that acts as a barrier to cross-border standardisation of administration. The administrative activities of the human resource and payroll functions are an important topic as most employees have predominantly transactional contact with these departments. Moreover, if the HR director fulfils the role of strategic business partner it is likely that in a time of increasing competition and economic difficulty the effectiveness and costs of administrative tasks become an area of attention.